Websites as Support Tools for Learning the English Language in Fergana State University - Ortiqov Rustamjon; Mo‘ydinov Shahboz (Peerian Journals Publishing, 2022)
In this article the usage of variety of websites to acquire among Uzbek students will be discussed in depth. The internet has a lot to offer the teacher. There are authentic resources and materials, places where you can find prepared lesson plans, ideas and worksheets. The advantages of the internet to teachers include the incredible expanse of the internet means the teacher has the ability to tailor lessons very specifically to students' needs and interests. Uzbek students tend to respond better when they feel involved and engaged in the subject and the extent of the web
Keywords: virtual learning; interactive websites; exposing learning sites; differentiation